Analysis of the population dinamics in Gödöllő district between 2005-2020 - Böhm, Zsanett; Nagyné Molnár, Melinda; Lőrinc , Balázs (Studia Mundi – Economica, 2022)
Each point or area of a geographical space has different, unique characteristics and attributes. Based on a framework of spatial differences that still exist today, the population dynamics analysis was implemented by means of a long time series analysis, covering the 15 municipalities of the Gödöllő district from 2005 to 2020. In connection with this, it can be stated that the deepening of territorial disparities within the country – even in the more developed regions – has led to increasing problems in recent decades, so that, based on the system of relations of territorial inequalities, the aim was to examine the social conditions of a district in the immediate vicinity of the capital city. The research provides a picture of spatial differences within the district that will have a major impact on the development of the region in the coming period and will also have a major impact on the society of the settlements in and near the Budapest agglomeration.